UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN KREATIF TEKS SASTRA PADA PESERTA DIDIK KELAS IV SDN DUREN SAWIT 02 MELALUI MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) - Tania Puti Khansa; Juhana Sakmal; Indah Wardatussa’idah (STKIP Subang, 2026)
This study aims to improve creative reading comprehension skills in literary texts among fourth-grade students (Class IV-A) of SDN Duren Sawit 02 through the Cooperative Integrated Reading and Composition (CIRC) model. This research is a classroom action research study employing the Kemmis and McTaggart model, conducted over two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 32 students of Class IV-A at SDN Duren Sawit 02. The study was conducted during the even semester of the 2025/2026 academic year. Research data were collected through tests, observation, and documentation. The results indicate an improvement in students' creative reading comprehension skills in literary texts. In Cycle I, 21 students achieved a score of ≥68, representing 65.62%, with teacher activity implementation reaching 77.5% and student activity reaching 76.7%. In Cycle II, the number of students achieving a score of ≥68 increased to 28 students, or 87.5%, with teacher activity implementation at 89.2% and student activity at 87.5%. Therefore, the implementation of the CIRC model can improve students creative reading comprehension skills in literary texts (short stories).